Mapping insights from global scientific literature on voter preferences and social media in elections - Yahya, Muhammad; Sinilele, Ahdan; Ibrahim, Ibrahim; Djamereng, Asni; Falah, A. Ilah Nurul; Baharuddin, Tawakkal (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
This research aims to comprehensively analyze the complex interactions between voter preferences, social media, and election dynamics by reviewing existing global research documents and identifying trends, key findings, and knowledge gaps that need to be filled. This research uses a bibliometric analysis approach with data from Scopus and the Vosviewer analysis tool to visualize the data. The main findings of this research show that political dynamics increasingly influenced by social media, especially related to the spread of fake news, polarization, and populism, significantly impact voter preferences. However, these three themes, namely fake news, polarization, and populism, still require deeper study in the future due to the lack of related research. In addition, to fill research gaps, it is also necessary to develop more sophisticated analytical models, including the application of artificial intelligence and voting algorithms, to understand the influence of new technologies in the political context and how this may shape voters' preferences in the future. The study also suggests implementing stricter policies, including increasing digital literacy and accountability of social media platforms, to ensure fairer and more transparent elections in the digital era. With these steps, it is hoped that future elections will be more honest, transparent, and free from the negative influence of social media.